Autonomous English Acquisition in Blended E-Studies for Adults for Sustainable Development: Implementation of the Synergetic System Model - Bojāre, Ināra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Researchers’ attention has moved from solving a problem to united methodology for solving different problems. It resulted in paradigm shift in the science and using system approach in social researches. The topicality of „Autonomous English acquisition in blended e-studies for adults for sustainable development”follows from results of the previous part of the research. They show that vertical hierarchy of responsibility has sticked together and learners’ interest towards methodological factors increased in virtual English acquisition. Next research problem is how to facilitate transformation of horisontal values from directed English acquisition to self-organised its acquisition in virtual learning environment. Hypothetically, it is assumed that there are sensitive factors, facilitation of which can call a resonance and transformation of other factors according to synergetic system model for facilitation the transformation of values in blended e-studies in adult nonformal education. The article presents reinterpretation of the results of the active research according to system approach of the whole research. The aim - to work out recommendations for implementation of the research model is reached in it.